1997
DOI: 10.1007/s002329900165
|View full text |Cite
|
Sign up to set email alerts
|

Cobra Venom Cytotoxin Free of Phospholipase A 2 and Its Effect on Model Membranes and T Leukemia Cells

Abstract: Membrane-active toxins from snake venom have been used previously to study protein-lipid interactions and to probe the physical and biochemical states of biomembranes. To extend these studies, we have isolated from Naja naja kaowthia (cobra) venom a cytotoxin free of detectable phospholipase A2 (PLA2). The amino acid composition, pI (10.2), and net charge of the cytotoxin compares well with membrane-active toxins isolated from venoms of other cobras. The cytotoxin, shown by a spin label method, associates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 29 publications
2
69
0
Order By: Relevance
“…1). These two effects are most likely related to the interactions of CTII with acidic phospholipids that are in direct contact with F 0 group proteins [14]. Such effects were not observed when DCCD-BP was added to mitochondria, possibly because hydrophobic DCCD-BP is incapable of interacting with mitochondrial membranes in an aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…1). These two effects are most likely related to the interactions of CTII with acidic phospholipids that are in direct contact with F 0 group proteins [14]. Such effects were not observed when DCCD-BP was added to mitochondria, possibly because hydrophobic DCCD-BP is incapable of interacting with mitochondrial membranes in an aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…These cytotoxins kill cells by non-selectively disrupting cell membranes [12,14]. Cytotoxins exhibit various physiological effects which are mainly regulated by modifying cell membrane structure and function [2,12,14,28,29].…”
Section: Epidemiology and Treatment Of Snake Envenomationmentioning
confidence: 99%
“…These cytotoxins kill cells by non-selectively disrupting cell membranes [12,14]. Cytotoxins exhibit various physiological effects which are mainly regulated by modifying cell membrane structure and function [2,12,14,28,29]. Various pharmacological applications have been suggested for cytotoxins such as their ability to destroy various types of cancer cells [2,12,14,30].…”
Section: Epidemiology and Treatment Of Snake Envenomationmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such synergistic enhancement includes cytotoxins from different cobra species. Cobra cytotoxins have been shown to enhance PLA2 activity through complex formation and deformation of cell membranes, causing cellular lysis due to hydrolysis of phospholipids (Gasanov et al, 1997, Gasanov et al, 2014. On a more toxin-specific level, Chaim-Matyas et al (1995) showed that cytotoxin P4 from Naja nigricollis (black-necked spitting cobra) venom acted synergistically with various PLA2s when cancer cell lines were subjected to these toxins in vitro, causing cell lysis.…”
Section: Supramolecular Synergismmentioning
confidence: 99%